Dealing with closed basins: the case of the lower Jordan River Basin - Venot, Jean-Philippe; Molle, Francois; Courcier, R. (2008)
During the past 50 years, the Lower Jordan River basin experienced a rapid and comprehensive process of development of its rare water resources. This led to its progressive closure; almost no water is left that can be mobilized and used while demand, notably in urban areas, keeps increasing. Despite the need to consider demand management options to alleviate the Jordanian water crisis, the potential of these options appears limited in the mid- term; the growing demand of the population and the sustaining of agriculture are unlikely to be met without supply augmentation measures which will reopen the basin.